Fish distribution in watersheds of the eastern part of the Serra da Mantiqueira (state of Sao Paulo) - Braga, F. M. S. [UNESP]; Carmassi, A. L.; Rondineli, G.; Lourenco, J. M. R. M. F. [UNESP] (Int Inst Ecology, 2014)
The present work aims to analyse jointly four contiguous watersheds in the eastern part of the Serra da Mantiqueira with respect to the distribution of fish fauna and physical structure. The watersheds of Piracuama river, Ribeirao Grande, Buenos and Guaratingueta are located in Pindamonhangaba, Campos do Jordao and Guaratingueta municipalities, in the state of Sao Paulo. Data were collected between the years 2001 and 2010, with collections distributed throughout the seasons, including sites located on the slope and piedmont. The limnological parameters analysed were different between watersheds and habitat structure was different only for the slope segments between Ribeirao Grande and Buenos watersheds, and between Ribeirao Grande and Piracuama watersheds. Thirty-five species of fish were caught, with the highest species richness found in the Ribeirao Grande watershed (30 species), followed by the Piracuama (23 species) and Buenos and Guaratingueta (21 species each). The most abundant species in both the segments (slope and piedmont) was Trichomycterus itatiayae. The highest degree of species dominance occurred in the Guaratingueta watershed and in the segment slope, being T. itatiayae the dominant species. Species diversity was lower at the slope than the piedmont, indicating variability in species abundance. Again T. itatiayae was the most abundant species in both segments, showing to be a well adapted species to these streams systems by presenting, as well as other species, morphological adaptations to the stream environment.

O presente trabalho tem por objetivo analisar conjuntamente quatro microbacias contíguas na serra da Mantiqueira oriental com respeito à distribuição da ictiofauna e estrutura física. As microbacias do rio Piracuama, do Ribeirão Grande, do ribeirão dos Buenos e do rio Guaratinguetá situam-se nos municípios de Pindamonhangaba, Campos do Jordão e Guaratinguetá, no estado de São Paulo. Os dados foram coletados entre os anos de 2001 e 2010, sendo as coletas distribuídas ao longo das estações e contemplando pontos localizados na encosta e no pediplano. Os parâmetros limnológicos analisados foram diferentes entre as microbacias e a estrutura de habitat foi diferente apenas para os segmentos de encosta entre as microbacias do Ribeirão Grande e Buenos, e entre Ribeirão Grande e Piracuama. Trinta e cinco espécies de peixes foram capturadas, sendo a maior riqueza de espécies encontrada na microbacia do Ribeirão Grande (30 espécies), seguida pela do rio Piracuama (23 espécies) e dos Buenos e Guaratinguetá (21 espécies cada). A espécie mais abundante tanto na encosta como pediplano foi Trichomycterus itatiayae. O maior grau de dominância de espécies ocorreu na microbacia do Guaratinguetá e no segmento de encosta, sendo T. itatiayae a espécie dominante. A diversidade de espécies para encosta foi inferior à do pediplano, indicando variabilidade na abundância das espécies. Novamente T. itatiayae foi a espécie mais abundante nos dois segmentos, espécie bem adaptada a esses sistemas de riachos por apresentar, assim como outras espécies, adaptações morfológicas ao ambiente de riachos torrentosos.
Distribuição de peixes em microbacias da serra da Mantiqueira oriental (Estado de São Paulo)
Keywords: Icthyofauna; Species diversity; Altitudinal gradient; Ictiofauna; Diversidade de espécies; Gradiente altitudinal